(untitled) (Journal of Asian Development Studies, 2021)
The purpose of this study is to find the relationship between economic growth on aid and trade. This study was conducted on low income and low middle-income countries around the world for the period of 1995 to 2019. Trade brings foreign reserve with the economic activity and aid bring foreign reserve that can be used to stimulate economic activity. Both can be significant if used in an appropriate and purposeful manner. So we tested two equations of aid and trade with the economic growth by applying fixed-effect test and random effect test. Although both tests showed significant results that means if the foreign reserve that is key to economic activity and key of connectivity with the foreign world to earn more foreign reserve can help in increasing the economic growth.